2013
DOI: 10.4067/s0717-97072013000200024
|View full text |Cite
|
Sign up to set email alerts
|

Lichens: Might Be Considered as a Source of Gastroprotective Molecules?

Abstract: Lichens are symbiotic relationship between fungi and algae or cyanobacteria. Secondary metabolites from lichens are known as lichen substances. We investigated depsidone and depside from lichens 1-6 in the context of their action to prevent gastric ulcer on the model of HCl/ethanol in mice for the first time. Doses of 30 mg/kg of lichen substances 1-6 and positive control (lansoprazole) significantly diminished the lesion index compared with negative control (treated only with HCl/EtOH). Lobaric acid 1, atrano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Buzgar et al [532] investigated fragments of a wall painting in Graeco-Roman contexts from the Beroe fortress, Romania (4-6th century), and identified a yellow-brown pigment as K-jarosite KFe 3+ 3 (OH) 6 (SO 4 ) 2 and/or Na-jarosite. Sepúlveda et al [533] studied yellow blocks from the archaeological site Playa Miller 7, on the coast of Atacama Desert in northern Chile, and reported the use of K-jarosite and natrojarosite in prehispanic times (approximately 2500 years BP). Pelosi et al, [534] using micro-Raman analysis, revealed the presence of jarosite in wall paintings in Cappadocia (Turkey).…”
Section: Yellow Pigmentsmentioning
confidence: 99%
“…Buzgar et al [532] investigated fragments of a wall painting in Graeco-Roman contexts from the Beroe fortress, Romania (4-6th century), and identified a yellow-brown pigment as K-jarosite KFe 3+ 3 (OH) 6 (SO 4 ) 2 and/or Na-jarosite. Sepúlveda et al [533] studied yellow blocks from the archaeological site Playa Miller 7, on the coast of Atacama Desert in northern Chile, and reported the use of K-jarosite and natrojarosite in prehispanic times (approximately 2500 years BP). Pelosi et al, [534] using micro-Raman analysis, revealed the presence of jarosite in wall paintings in Cappadocia (Turkey).…”
Section: Yellow Pigmentsmentioning
confidence: 99%
“…2011), gastroprotective (Sepulveda et al . 2013) and analgesic (Bugni et al . 2009) properties as well as wound healing (Barreto et al .…”
Section: Introductionmentioning
confidence: 99%
“…Less frequently, atranorin has been noted as a herbivore deterrent (Pöykkö et al 2005;Nimis & Skert 2006), an inhibitor of competitive species (Whiton & Lawrey 1984) and a reducing agent to facilitate iron and phosphate uptake in acidic soils (Paul et al 2009). Atranorin also has many potential human health applications, including anticancer (Bačkorová et al 2012), antimicrobial (Türk et al 2006;Kosanić et al 2013), prooxidant and antioxidant (Melo et al 2011), gastroprotective (Sepulveda et al 2013) and analgesic (Bugni et al 2009) properties as well as wound healing (Barreto et al 2013), biofilm inhibition (Pompilio et al 2013) and mosquito abatement as a larvicide (Cetin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cardiovascular protective activity of PSA detected presence of the antioxidant capacity was also included in the results of the same study. Another study on the protective effect of PSA was carried out on mice and the gastric protective effect of PSA was determined (Sepulveda et al 2013). In the studies related with toxic concentrations of PSA, inhibition of growth as determined in different bacteria species (Celenza et al 2013;Mitrović et al 2014), liver parasites (Lauinger et al 2013) and some cancer cells (Correcché et al 2004;Brandao et al 2013) exposed to PSA.…”
Section: Discussionmentioning
confidence: 99%